Penerapan Model Kooperatif Tipe Team Games Tournament dalam Volley Ball Like Games - Ramadhan, Refky Sudrajat (TEGAR: Journal of Teaching Physical Education in Elementary School, 2019)
This study aims to find out if the TGT (Team Games Tournament) cooperative model through volley ball like Games can improve your volleyball mini play skills. Research using class action research method, with participants is VB class student SDN 178 Gegerkalong KPAD Bandung City, which amounted to 30 students (16 male; 13 female). The research Data is taken using the Games Performance Assessment Instrument (GPAI) assessment format. The results showed an increase in the average pre-test that the student received was 69, and on the average final cycle of the student's value of 78. Thus, the results can be concluded that the implementation of TGT type cooperative model through volley-like games can improve the playing skills of Minivolleyball in grade V students at SDN Gegerkalong KPAD in Bandung.Â AbstrakStudi ini bertujuan untuk mengetahui apakah model kooperatif tipe TGT (Team Games Tournament) melalui volley ball like games dapat meningkatkan keterampilan bermain mini voli. Penelitian menggunakan metode penelitian tindakan kelas, dengan partisipan adalah siswa kelas VB SDN 178 Gegerkalong KPAD Kota Bandung, Yang berjumlah 30 siswa (16 laki-laki; 13 perempuan). Data penelitian diambil dengan menggunakan format penilaian Games Performance Assessment Instrument (GPAI). Hasil penelitian ini menunjukan adanya peningkatan, rata-rata nilai pada pre-test yang diperoleh siswa sebesar 69, dan pada siklus akhir rata-rata nilai siswa sebesar 78. Dengan begitu dari hasil dapat disimpulkan bahwa penerapan model kooperatif tipe TGT melalui volley-like games dapat meningkatkan keterampilan bermain minivoli pada siswa kelas V SDN Gegerkalong KPAD Kota Bandung.Â